Alkenylidenecyclopropanes in synthesis - Cairns, Peter M. (1982)
This thesis reports an investigation into the synthetic potential of alkenylidenecyclopropanes, with particular emphasis on bicyclic and tricyclic systems. In Chapter 1 alkenylidene carbenes and alkenylidenecyclopropanes are briefly reviewed. The bicyclic alkenylidenecyclopropanes obtained by additicn of 2-meth711-propenylidenecarbene to cyclopentene, cyclohexene, 1-methylcyclohexene, methylenecyclohexane, dihydrofuran and dihydropyran, and the tricyclic alkenylidenecyclopropanes obtained from alpha- and beta-pinene, were the pivotal molecules of our research. Chapter 2 reports the synthesis of these compounds along with a number of functionalised systems. Also described are unsuccessful attempts to prepare carbene precursors for a projected intramolecular carbene synthesis of the sesquiterpene, bicyclogermacrene. Chapter 3 details the acid catalysed reactions of alkenylidenecyclopropanes. Alkenylidenecyclopropanes having a fused six membered ring gave mainly cyclopropane ring opened acetylenes arising from initial electrophilic attack at the terminal C-5 carbon atom of the allene system. Minor products formally derived by trapping of cyclopropyl cations arising from C-1; attack were also isolated. However, in the case of the alkenylidenecyclopropane obtained from cyclopentene only ring expanded products resulting from initial attack at C-4 were isolated. The C15 alkenylidenecyclopropanes obtained fro=o(gamma- and beta-pinene gave ring opened monocyclic enynes possessing a menthane type skeleton. Mechanisms are proposed to account for all the products isolated. In contrast to previous studies in this area the same products were obtained on changing from Lewis to protic acid. A new route to 3-substituted gamma- and delta-lactones from dihydrofuran and dihydropyran respectively is given. Under Lewis acid catalysed conditions allylidenecyclopropanes gave exclusively the same major products obtained on acid catalysed reaction of the parent alkenylidenecyclopropanes. In Chapter 4 the peracid oxidation of alkenylidenecyclopropanes has been extended to bicyclic systems. The stereochemistry of the resulting ketoesters and derived products are discussed. The dissolving metal reduction of bicyclic and tricyclic alkenylidenecyclopropanes is shown to be regiospecific and stereoselective affording vinylcyclopropanes of predominantly exo stereochemistry. Chapter 5 describes the reaction of alkenylidenecyclopropanes with thiophenol to give regioselectively and stereoselectively endo cyclopropyl enol thioethers. Reductive cleavage gave vinylcyclopropanes; together with the dissolving metal reduction of the parent alkenylidenecyclopropanes providing a stereoselective route to vinylcyclopropanes from alkenes. A novel synthesis of the seven membered ring monoterpenoid, karahanaenone via Cope rearrangement of a thiodivinylcyclopropane is described